NEW R2NH2OH (R = Cy, Bu) ADDUCTS OF MX2, MX3 OR MX5: SYNTHESIS AND INFRARED STUDY - NDONGO GUEYE; LIBASSE DIOP; LAMINE DIOP (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
When Cy2NH and Bu2NH in the presence of a very little amount of water are allowed to react with metal halide CdBr2, SbCl3 or SbCl5, hydroxyl adducts with protonated amines as adverse cations were obtained. Their infrared study allows concluding the presence of OH- linked to the metallic center.